Model of the Formation of a Fixed Charge in SiO2, Produced by Thermal Oxidation of Silicon - U. A. Pilipenka; H. A. Amelchanka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Solid-state recrystallization of the surface silicon layer after chemical and mechanical polishing with application of fast thermal treatment by pulses of one second duration is one of the feasible methods of improving the silicon surface properties. The purpose of this work is to explore the impact of fast thermal treatment resulting in solid state recrystallization of mechanically disrupted layer on generation of fixed charge in SiO2 at thermal oxidation of silicon. The results of studying P-doped electron silicon (KEF 4.5) and B-doped hole silicon (BDS 12) hole-type silicon of orientation <100> diameter 100 mm after chemical and mechanical polishing are provided. By the method of voltage-capacitance characteristic the flat zones voltage and charge density on the boundary of “silicon – silicon dioxide” were determined and by the method of scanning probe electrometry the surface distribution of these characteristic prior and after fast thermal treatment was determined. It has been ascertained that fast thermal treatment on silicon wafers KEF 4.5 and BDS 12 of orientation <100> due to solid state recrystallization of mechanically disrupted layer shall bring about 1.5 times decrease in surface potential along wafers area and residual fixed charge in silicon dioxide.